Advisory role of music: Textual analysis of Nelly Uchendu Waka About Song - Alemede, Emmanuel Oyetunji (Journal of Gender and Power, 2023)
This paper provides a textual analysis of the song “Waka About” by Nelly Uchendu. The song is a cautionary tale that advises women to be discerning when it comes to men who appear to be “lazy” and who want to get married. The analysis examines the lyrics of the song to uncover the underlying message and to better understand the role of music in providing an advisory role. It is argued that the song is an effective strategy to communicate a message of caution to women and to provide a form of guidance. The findings suggest that music has a powerful ability to engage the audience and to impart knowledge and advise. The song conveys a strong message that encourages women to be discerning when it comes to marriage. It is not enough to conclude on marrying a man base on material wealth, his appearance (good looking) rather there is a need to investigate the man’s past life, his current lifestyle, his job or profession. Listening to music, individuals can gain insight into the values and norms of their society, thus providing a way for them to achieve a successful and fulfilling life. Songs like waka about should also be used as part of materials during counselling sections and more songs should be written or composed to serve advisory instruments in all matters that deals with of life as music is an effective tool in transmission of knowledge.